Extraction of Outer Membrane Proteins of Proteus Mirabilis Isolated From Urinary Tract Infections and their Immunological Effect In Vitro - Heba safaa Abdelqader; Ibrahim A. A. Rahmman (Indian Journal of Forensic Medicine & Toxicology, 2022)
300 urine samples were collected from patients visiting Fallujah city hospitals (consulting clinicsof Fallujah Teaching Hospital and Women and Children Hospital) for the period from 1/9/2020 to30/12/2020, of different ages and for both sexes. The results showed that out of 300 urine samples were244(81.33%) A sample with a positive result for bacterial culture, and it was found there were highsignificant differences between the positive and negative cultures. Females and males (64.70) (35.29),respectively.Isolates of Proteus mirabilis were diagnosed by observing the cultivar (colonies) and microscopic(bacterial cells) characteristics, biochemical tests and diagnostics with Vitek device. Antibiotic sensitivitywere done at 12 types, Antibiotic resistance wre vary from Cefotaxime, Rifampicin, Ceftriaxon (100%),Cefixime, Ciprofloxacin (76.4%), Levofloxacin (64.7%), Nitrofurantoin (58.8%), Gentamicin (52.9%),Amikacin, Nalidixic acid (35.2%) (17.6%) Imipenem (11.7%).Extraction and partial purification of outer membrane proteins (OMPs) from the most antibioticresistantisolate using lysozyme, DNase, RNase, and N-Lauroyl-Sarcosinate enzymes. associated withthe ion exchanger.To study the effect of the antigen of outer membrane proteins, some immunoassays were performedin vitro and the following results appeared: The use of concentrations (100, 50, 25) of OMPs antigenled to low significant of lymphocyte viability percentage (96.66, 97.66,98.0), respectively compared toWith the negative control (99.66), the concentrations (100,50)% significantly reduced the percentageof survival of PMNs cells (97.66,98.33), respectively, compared with the control (99.66), while theconcentration of 25 did not affect the survival of PMNs cells (99.66). The above concentrations showeda low significant in the diameter of the migration circuit of PMNs cells (8.830,10.59,12.21) comparedwith the negative control (15.21), while these concentrations led to a high significant in the percentageof formazone-forming PMNs cells (64.66,58.0,47.0) compared with the control (36.66). ) and a highsignificant in the sensitivity of lymphocytes (4.0,3.39,1.87), as the absorption spectrum values forconcentrations (100,50,25) reached (0.92,0.74,0.41), respectively, compared with the negative control(0.22) and the positive control (1.53). The concentrations of the used proteins increased the phagocyticindex (PI) of PMN cells ,The phagocytosis coefficient was high significantly with time until it reached itsmaximum at 90 minutes, and from the statistical analysis it was found that the phagocytosis coefficientincreases with increasing concentration of proteins.